Concrete Brick Utilizing By-products of Recycled Aggregates and Method for Manufacturing the Same

KR103021390B1Active Publication Date: 2026-09-18DONGBU ENT
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020260020606
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-02-02
Publication Date
2026-09-18
Estimated Expiration
2046-02-02

Smart Images

  • Figure 112026013855611-PAT00001
    Figure 112026013855611-PAT00001
Patent Text Reader

Abstract

The present invention relates to concrete bricks utilizing recycled aggregate by-products and a method for manufacturing the same, wherein stone powder and recycled concrete fine powder, which are waste materials generated during the intermediate processing of recycled aggregates, are used as materials for the bricks. The concrete brick utilizing recycled aggregate by-products according to the present invention comprises cement, stone powder recovered from the crushing of rocks or intermediate treatment of waste concrete, and recycled concrete fine powder recovered from the recycling process of construction waste or waste concrete or the production process of recycled aggregates, wherein the composition comprises 8-11% by weight of cement, 89-92% by weight of stone powder, and 28-32 parts by weight of recycled concrete fine powder per 100 parts by weight of cement. The method for manufacturing the concrete brick utilizing recycled aggregate by-products according to the present invention comprises a first step of mixing cement, stone powder, and recycled concrete fine powder, and performing a first curing under conditions of a temperature (T) of 20℃±10%, a relative humidity (RH) of 30-40%, and a curing time of 23-25 ​​hours; and includes a second step of second carbonation curing of the primary cured organism produced through the first step above under conditions of temperature (T) 20℃±10%, relative humidity (RH) 75~85%, curing time 68~74 hours, and carbon dioxide concentration 4~7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to concrete bricks, and more specifically, to concrete bricks utilizing recycled aggregate by-products that replace aggregates while minimizing the amount of cement used, and a method for manufacturing the same. Background Technology

[0002] Concrete bricks are manufactured by mixing aggregates such as cement, sand, and gravel with water, and then molding and curing the mixture. While these concrete bricks have the advantages of being relatively easy to manufacture and having excellent strength, they present problems such as high carbon dioxide emissions and significant resource consumption due to the large amount of cement used.

[0003] In addition, concrete bricks composed of a single material are vulnerable to external environments (wear, impact, moisture penetration, etc.) and have limitations, such as cracking or deterioration occurring during long-term use.

[0004] Meanwhile, in order to recycle resources and reduce environmental burden, numerous technologies have been proposed to crush waste concrete and use it as recycled aggregate. Technologies have also been disclosed for crushing waste concrete to produce recycled aggregate or fine powder, and mixing it into concrete blocks or bricks.

[0005] However, most conventional technologies are limited to simply mixing waste concrete materials as substitutes for general aggregates or fillers, and suffer from the problem of failing to fully utilize the reactivity or functional characteristics of recycled fine powder. In particular, issues such as reduced strength, quality variations, and increased water absorption rates resulting from the use of recycled materials have been continuously raised.

[0006] In addition, stone powder generated during the crushing process is an inorganic powder containing fine particles, and in some conventional technologies, it has been used as a filler for concrete or mortar. However, if the stone powder is uniformly mixed throughout the concrete, problems such as reduced workability, increased water requirements, and quality variations may occur, and there is a limitation in that the role of the stone powder is limited to that of a simple filler.

[0007] The problems of the conventional technology can be summarized as follows.

[0008] The high usage of cement places a heavy burden on the environment.

[0009] The material properties are not fully utilized by simply mixing recycled fine powder or stone powder.

[0010] It is difficult to satisfy both the external durability and internal strength of concrete bricks at the same time.

[0011] When using recycled resources, quality variations and long-term durability degradation occur.

[0012] The functional division by layer is not clear, resulting in low freedom in performance design.

[0013] Therefore, a new concrete brick structure and manufacturing method are required that can effectively utilize recycled resources such as recycled fine powder and stone powder while simultaneously improving the structural performance and durability of concrete bricks.

[0014] In particular, there is a need to develop a technology that can maximize the functionality of the material and ensure quality stability by separating the inner and outer layers into different material compositions and sequentially molding and curing each layer.

[0015] Registered Patent No. 10-2241908 involves mixing waste gypsum powder, waste artificial marble powder, etc., to reduce the specific gravity of cement; Registered Patent No. 10-1807950 utilizes waste paper; and Registered Patent No. 10-2256220 utilizes waste plastic. Prior art literature

[0016] Registered Patent No. 10-2241908 Registered Patent No. 10-1807950 Registered Patent No. 10-2256220 The problem to be solved

[0017] The present invention aims to solve the aforementioned problems by providing a concrete brick utilizing recycled aggregate by-products and a method for manufacturing the same, wherein stone powder and recycled fine powder, which are waste materials generated during the intermediate processing of recycled aggregates, are used as brick materials. means of solving the problem

[0018] The concrete brick utilizing recycled aggregate by-products according to the present invention is composed of cement, stone powder recovered from the crushing of rocks or intermediate treatment of waste concrete, and recycled concrete fine powder recovered from the recycling process of construction waste or waste concrete or the production process of recycled aggregate, and is characterized by a composition comprising 8-11% by weight of cement, 89-92% by weight of stone powder, and 28-32% by weight of recycled concrete fine powder per 100% by weight of cement.

[0019] The method for manufacturing a concrete brick using recycled aggregate by-products according to the present invention comprises: a first step of mixing cement, stone powder, and recycled concrete fine powder, and performing a first curing under conditions of a temperature (T) of 20℃±10%, a relative humidity (RH) of 30~40%, and a curing time of 23~25 hours; and a second step of performing a second carbonation curing under conditions of a temperature (T) of 20℃±10%, a relative humidity (RH) of 75~85%, a curing time of 68~74 hours, and a carbon dioxide concentration of 4~7%. Effects of the invention

[0020] The concrete brick utilizing recycled aggregate by-products and the method for manufacturing the same according to the present invention have the following effects.

[0021] The mixing of stone powder forms a skeletal structure with a stable particle size distribution, which has the effect of improving the compressive strength and durability of concrete bricks.

[0022] Furthermore, it contributes to carbon reduction by promoting carbonation reactions and fixing carbon dioxide through the mixing of recycled fine powder.

[0023] In addition, by reducing cement usage and replacing it with natural aggregate (sand), resources are conserved compared to using sand, and economic viability is secured through the creation of added value from waste recycling.

[0024] In addition, the double structure of the core layer and the skin layer further enhances structural stability and carbon dioxide fixation effects, and improves the reliability of concrete bricks. Specific details for implementing the invention

[0025] In the following description of the present invention, specific descriptions of related known functions or configurations will be omitted if it is determined that such descriptions would unnecessarily obscure the essence of the invention. Furthermore, the terms described below are defined in consideration of their functions within the present invention, and these definitions may vary depending on the intentions or practices of the user or operator. Therefore, such definitions should be based on the content throughout this specification.

[0026] The present invention includes Example 1 of a single curing type composed of cement, rock crushed sand (RCS), and recycled fine powder (hereinafter referred to as 'recycled fine powder') (RFP, Recycled Fine Powder), and Example 2 of a double curing type composed of cement, rock crushed stone (RCS) and / or recycled fine powder (RFP, Recycled Fine Powder).

[0027] First, the composition of cement, stone powder (RCS), and recycled fine powder (RFP) will be explained.

[0028] 1. Cement.

[0029] The cement is Type 1 Ordinary Portland Cement (OPC), but of course, it is not limited to this, and various types of cement that satisfy various KS standards can be used.

[0030] 2. Stone powder (RCS).

[0031] Stone powder is generated during the production process of recycled aggregates (such as rock crushing or intermediate treatment of waste concrete) and serves as a replacement for conventionally used recycled sand (RS); it possesses the following characteristics.

[0032] Particle size 6~8mm, surface-dry specific gravity 2.26~2.35, oven-dry specific gravity 2.04~2.19, water absorption 7.4%~10.6%

[0033] 3. Circulated fine powder (RFP).

[0034] Recycled fine powder is a recycled fine powder generated during the intermediate treatment of waste concrete (the recycling process of construction waste or waste concrete or the production process of recycled aggregate), and is used as a filler for concrete bricks. Its characteristics include a particle size of 0.6 to 1 mm, a surface dry specific gravity of 2.06 to 2.08, an oven dry specific gravity of 1.79 to 1.84, and an absorption rate of 11.7% to 15.9%.

[0035] The chemical composition (XRF, X-ray fluorescence) of stone powder and recycled fine powder is as shown in Table 1 below.

[0036]

[0037] The CaO content of stone powder (RCS) and recycled fine powder (RFP) is 49.0% and 22.4%, respectively, showing high content, so it was found to be suitable for the application of CCU technology to form calcium carbonate (CaCO3) by reacting with carbon dioxide (CO2) as shown in Equation (1) below.

[0038] CaO + CO2→ CaCO3----------------Equation (1)

[0039] Although recycled fine powder has a lower total CaO content than stone powder, it is advantageous for carbon dioxide fixation because it has a relatively high reactive CaO content, a large particle surface area, and a porous structure.

[0040] <Example 1>

[0041] The concrete brick utilizing recycled aggregate by-products according to the present embodiment has a mixing ratio of 8-11% by weight of cement, 89-92% by weight of stone powder, and 28-32% by weight of recycled fine powder per 100% by weight of cement, and the above mixing ratio is an optimal ratio for inducing the inherent roles of the materials and enhancing their roles through harmony between the materials.

[0042] Cement is used to bind materials, and if mixed at less than 8 weight percent, the binding strength is weak, but even if it does not exceed 11 weight percent, sufficient binding strength can be secured through stone powder and recycled fine powder.

[0043] Stone powder acts as a load-bearing framework in concrete bricks; in addition to fulfilling the role of sand by securing compressive strength, suppressing shrinkage deformation, and improving shape stability, it forms a micro-framework and also plays a role in surface densification.

[0044] The cement to stone powder volume ratio with minimized cement usage may be 1:9.0 to 9.8.

[0045] Circulated fine powder participates in the chemical reactions of materials to contribute to the development of initial and long-term strength and forms recombination within the pores. It contributes to reducing cement usage through its bonding strength, and also contributes to reducing porosity, lowering water absorption, and improving durability through its fine particle size. Additionally, it fixes carbon dioxide through reactions with carbon dioxide and its pore structure. If it is less than 28 parts by weight per 100 parts by weight of cement, the effects such as bonding strength are weak, and if it exceeds 32 parts by weight, it can reduce the bonding strength of the cement.

[0046] Water is used to bind the materials, and the mixing ratio (w / b) of water (w) and cement (b) is 0.70 to 8.5 by weight, and preferably 0.8.

[0047] The method for manufacturing (curing) concrete bricks according to the present embodiment is as follows.

[0048] 1. First curing.

[0049] Cement, stone powder, and recycled fine powder are mixed, and this concrete brick composition is placed in a formwork and air-dried cured. The air-dried curing conditions are a temperature (T) of 20℃±10%, a relative humidity (RH) of 30~40%, and a curing time of 23~25 hours.

[0050] CSH and Ca(OH)2 are formed as major compounds during air-dry curing of concrete.

[0051] The first curing is for durability and shape stabilization, and also, as a condition for the second carbonation curing, the first curing is cured in a state where the moisture content of the first curing is 5~8%.

[0052] 2. Secondary carbonation curing.

[0053] The primary curing process for fixing (absorbing) carbon dioxide is as follows: temperature (T) 20℃±10%, relative humidity (RH) 75~85%, curing time 68~74 hours, and carbon dioxide concentration 4~7%.

[0054] After concrete carbonation curing, some of the major compounds react with carbon dioxide to form calcium carbonate (CaCO3).

[0055] To verify the performance of the concrete brick according to the present embodiment, it was manufactured and tested as follows.

[0056] 1. Composition.

[0057] 9% by weight of cement, 91% by weight of stone powder, 30 parts by weight of recycled fine powder (based on 100 parts by weight of cement), cement / water ratio 0.80.

[0058] 2. Manufacturing.

[0059] A concrete brick composition having the aforementioned composition was mixed and placed into a formwork (50 mm * 50 mm * 50 mm), and then first air-dry curing was performed in a curing device (temperature 20℃, relative humidity (RH) 30%, curing time 24 hours), and the first cured product, after completing the first air-dry curing, was subjected to second carbonation curing (temperature 20℃, relative humidity (RH) 75%, curing time 72 hours, carbon dioxide concentration 5%).

[0060] 3. Exam.

[0061] A. Packing density test.

[0062] When mixing constituent materials such as cement and aggregates for the manufacture of concrete and mortar, the importance of packing density testing—which determines the particle size and usage ratio of each constituent material to ensure that each material has minimal space in a dry mixing state without water—is increasingly being recognized. Packing density testing is particularly utilized as a crucial concept in the manufacture of high-strength concrete / mortar with a compressive strength of 60 MPa or higher and ultra-high-performance concrete with a compressive strength of 100 MPa or higher. In this invention, the experimental packing density methodology proposed by Li & Kwan (2014) was used, and the results are as follows.

[0063] The porosity and the actual volume have the following relationship.

[0064] Porosity + Actual volume = 1

[0065] solid ratio void ratio loose rodded vibrated loose rodded vibrated 0.6588 0.7578 0.7969 0.3412 0.2422 0.2031

[0066] For the three different compaction methods, the order was always vibrated > rodded > loose, and it was confirmed that the performance rate (79.69%) was high during vibrated compaction, which exhibited the highest performance rate (lowest void ratio). In addition, the void ratio of this example was 0.2031 (20.31%), showing excellent results with the highest performance rate and lowest void ratio.

[0067] B. Hardened concrete strength development test.

[0068] In the process of manufacturing through the aforementioned manufacturing process, a compressive strength test was performed on specimens cured under two different conditions at ages 7 and 28.

[0069] division 7 days Compressive strength ratio 28th Compressive strength ratio Comparative Example 1 8.9 100% 12.0 100% Comparative Example 2 10.7 120% 11.8 98.9% Comparative Example 3 10.8 122% 11.8 98.9% This embodiment 13.4 150% 13.8 116%

[0070] Comparative Example 1: Composed of cement and stone powder (no mixed recycled fine powder) and air-dried curing

[0071] Comparative Example 2: Composed of cement, stone powder, and recycled fine powder, and air-cured

[0072] Comparative Example 3: Composed of cement and stone powder (no mixed recycled fine powder), followed by primary air-drying curing and secondary carbonation curing.

[0073] This example showed a compressive strength of 13.4 MPa, and it was confirmed that it exhibited compressive strengths of 122% and 150%, respectively, compared to Comparative Example 1.

[0074] C. Absorption rate.

[0075] This example was confirmed to have an absorption rate of 13% after secondary carbonation curing.

[0076] D. Microstructure Analysis.

[0077] Microstructure analysis capable of investigating the carbonation effect was performed using XRD and TGA / DTG, and analysis was conducted on Comparative Examples 1, 2, and 3 and Examples with w / b = 0.8. Here, XRD can investigate the mineral composition before and after carbonation, respectively, and TGA / DTG can quantitatively evaluate the CaCO3 content before and after carbonation.

[0078] (1) X-ray diffraction analysis (XRD)

[0079] XRD analysis results showed that in the example where carbonation curing was performed for 72 hours, the calcium carbonate peak at 2θ = 30 degrees showed a distinct tendency to increase compared to Comparative Example 2, where carbonation curing was not performed. The same result was also confirmed by comparing the analysis results of Comparative Examples 1 and 3.

[0080] (2) Thermogravimetric analysis (TGA / DTG)

[0081] After carbonation curing, the carbon dioxide adsorption amount was confirmed to be 4.0~4.8%, which is close to the carbonation adsorption amount of pure fine powder, 5.55%.

[0082] <Example 2>

[0083] This embodiment is the same as Example 1 in that it uses materials of cement, stone powder (RCS), and recycled fine powder (RFP), but it differs in that the concrete brick has a double structure (core layer, skin layer) inside and outside, and the composition of the core layer and the skin layer are different.

[0084] The core layer (inner layer) is composed of cement and recycled fine powder for reactivity, carbonation, and strength development, and consists of 28 to 32 parts by weight of recycled fine powder per 100 parts by weight of cement (the cement / water ratio is the same as in Example 1).

[0085] The core layer is manufactured by primary air-drying and secondary carbonation curing as described above to fix carbon dioxide, and is manufactured by vibrating. The conditions for primary air-drying and secondary carbonation curing are the same as in Example 1.

[0086] The outer layer (outer layer) is composed of cement and stone powder for skeletal formation, wear resistance, and shape stabilization, preferably with a composition of 8-11% by weight of cement and 89-92% by weight of stone powder (the cement / water ratio is the same as in Example 1).

[0087] The surface layer prevents damage caused by load when concrete bricks are used in masonry, and can enhance the carbon dioxide fixation effect by isolating the core layer, where carbon dioxide is fixed, from the outside.

[0088] Since the epidermal layer does not require carbonation, it is manufactured by general curing (air-dry curing) without undergoing carbonation curing, and is produced by rodded or loose filling.

[0089] The core layer is in the shape of a cuboid, and the epidermal layer may be formed on all six sides outside the core layer, but is not limited thereto, and may be formed on only five sides so that one side of the core layer is exposed to the outside.

[0090] A method for manufacturing a double-layered concrete brick involves pouring and curing a core layer and pouring and curing a skin layer on the outside of the core layer. It is possible to pour the skin layer after the core layer is fully cured, or to pour and cure the skin layer before full curing (e.g., 90% curing). In the latter case, separation between the core layer and the skin layer can be prevented.

[0091] Alternatively, to secure interfacial bonding strength between the core layer and the skin layer, it is also possible to cure the core layer and roughen its surface before casting the skin layer.

[0092] Meanwhile, in this embodiment, it is also possible to include cement, stone powder, and recycled fine powder as compositions for the core layer and the skin layer, and to vary the mixing ratio according to the function of the core layer and the skin layer.

[0093] The core layer is composed of 25-30% by weight of cement, 60-70% by weight of recycled fine powder, and 5-15% by weight of stone powder, based on 100% by weight of the total.

[0094] The surface layer is composed of 8-11% by weight of cement, 89-92% by weight of stone powder, and 5-15% by weight of recycled fine powder per 100% by weight of cement.

[0095] The above composition is intended to prevent a decrease in the strength of the epidermal layer and increase the amount of carbon dioxide fixed while maintaining the functions of the core layer and the epidermal layer.

[0096] In the case of such a composition, since both the core layer and the epidermal layer contain circulating fine powder, it is manufactured through primary air-drying curing and secondary carbonation curing, and each curing condition is carried out from the curing conditions described above.

[0097] This embodiment also confirmed results at the same level as those demonstrated in Example 1.

Claims

Claim 1 A concrete brick utilizing recycled aggregate byproducts, characterized by having a double structure of a core layer and a skin layer composed of cement, stone powder recovered from the crushing of rocks or intermediate processing of waste concrete, and recycled concrete fine powder recovered from the recycling process of construction waste or waste concrete or the production process of recycled aggregates, wherein the stone powder has a particle size of 6~8mm and an absorption rate of 7.4%~10.6%, the core layer is manufactured by first air-drying curing to a state where the moisture content is 5~8% while having a composition of 28~32 parts by weight of recycled concrete fine powder per 100 parts by weight of cement, followed by second carbonation curing, and the skin layer is manufactured by air-drying curing while having a composition of 8~11% by weight of cement and 89~92% by weight of stone powder per 100% by weight of the total, and retaining carbon dioxide by isolating the core layer from the outside. Claim 2 delete Claim 3 A concrete brick utilizing recycled aggregate byproducts, characterized by having a double structure of a core layer and a skin layer composed of cement, stone powder recovered from the crushing of rocks or intermediate processing of waste concrete, and recycled concrete fine powder recovered from the recycling process of construction waste or waste concrete or the production process of recycled aggregates, wherein the stone powder has a particle size of 6~8 mm and an absorption rate of 7.4%~10.6%, the core layer is manufactured by first air-drying curing to a state where the moisture content is 5~8% and then second carbonation curing, with a composition of 25~30% by weight of cement, 60~70% by weight of recycled concrete fine powder, and 5~15% by weight of stone powder based on 100% by weight of the total, and the skin layer is manufactured by air-drying curing while having a composition of 8~11% by weight of cement, 89~92% by weight of stone powder, and 5~15% by weight of recycled concrete fine powder based on 100% by weight of cement. Claim 4 delete Claim 5 A concrete brick utilizing recycled aggregate by-products according to claim 1, characterized in that the recycled concrete fine powder has a particle size of 0.6 to 1 mm and an absorption rate of 11.7% to 15.9%. Claim 6 A method for manufacturing concrete bricks utilizing recycled aggregate by-products according to claim 1, comprising: a core layer manufacturing step of manufacturing a core layer by pouring a composition comprising 28 to 32 parts by weight of recycled concrete fine powder per 100 parts by weight of cement, performing a first air-dry curing until the moisture content is 5 to 8%, and then performing a second carbonation curing; and a skin layer manufacturing step of manufacturing a skin layer by pouring a composition comprising 8 to 11% by weight of cement and 89 to 92% by weight of stone powder per 100% by weight of the total on the surface of the core layer and then performing air-dry curing, wherein the core layer manufacturing step comprises manufacturing a first cured material by performing first air-dry curing under conditions of temperature (T) 20℃±10%, relative humidity (RH) 30 to 40%, and curing time 23 to 25 hours, and the first cured material under conditions of temperature (T) 20℃±10%, relative humidity (RH) 75 to 85%, and curing time A method for manufacturing concrete bricks using recycled aggregate by-products, characterized by secondary carbonation curing for 68 to 74 hours under conditions of a carbon dioxide concentration of 4 to 7%.

Citation Information

Patent Citations

  • Manufacturing methods of environmental friendly high performance concrete for retaining wall using waste concrete powder, recycled aggregates and industrial by-products and environmental friendly retaining wall block manufactured by using it

    KR100582770B1

  • Omitted

    KR1020160009139A

  • Eco-friendly loess porous block and the method of manufacturing the same

    KR101440407B1

  • Retaining wall block for sequestration of carbon dioxide, and manufacturing method for the same

    KR1020250082061A